2009
DOI: 10.7863/jum.2009.28.7.889
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Screening for Major Congenital Heart Disease

Abstract: Objective. The purpose of this study was to determine the relative importance of the 4-chamber view (4CV) compared with the outflow tract views (OFTVs) in prenatal screening for major congenital heart disease (CHD). Methods. We prospectively evaluated 200 consecutive infants undergoing cardiac surgery at our institution for major CHD. By reviewing the infants' medical records and conducting bedside interviews with their parents or guardians, we evaluated detection rates both prenatally and postnatally (before … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(27 citation statements)
references
References 41 publications
0
26
0
1
Order By: Relevance
“…During the timeframe of this study, basic fetal cardiac screening relied mostly on a 4CV 30,31 and this likely contributes to our findings of low detection rates for defects such as TGA, TOF and DORV which require OFTVs for diagnosis. It has been shown that OFTVs are more likely to be abnormal in mid-gestation screening for fetuses with critical forms of CHD while 4CV detect smaller percentage of critical CHD cases 10 . Recently, obstetrical guidelines have been updated to recommend OFTVs in addition to the 4CV during second trimester screening ultrasound 32 .…”
Section: Discussionmentioning
confidence: 99%
“…During the timeframe of this study, basic fetal cardiac screening relied mostly on a 4CV 30,31 and this likely contributes to our findings of low detection rates for defects such as TGA, TOF and DORV which require OFTVs for diagnosis. It has been shown that OFTVs are more likely to be abnormal in mid-gestation screening for fetuses with critical forms of CHD while 4CV detect smaller percentage of critical CHD cases 10 . Recently, obstetrical guidelines have been updated to recommend OFTVs in addition to the 4CV during second trimester screening ultrasound 32 .…”
Section: Discussionmentioning
confidence: 99%
“…3 Yet, the prenatal detection of CHD has remained challenging, with the sensitivity of ultrasound ranging from 15–39%. 412 This has been attributed mainly to operator skill and expertise; 1318 however, other factors include the complex anatomy, motion, and small size of the fetal heart. The lack of prenatal identification of CHD is associated with adverse consequences for the neonate, including abnormal neurological development, and even death.…”
Section: Introductionmentioning
confidence: 99%
“…Also, AIUM has proposed similar guidelines [ 28 , 29 ]. It is therefore a very important step in improving detection of CHD by complementing the 4CV with the outflow tract views under these guidelines, as documented by several teams and regional studies [ 13 , 15 ]. Theoretically, most cardiac anomalies can be detected if all the planes could be acquired and the image data interpretations are made correctly.…”
Section: Discussionmentioning
confidence: 99%
“…A symmetric four-chamber view (4CV) has been used to confirm a normal fetal heart since the early 1990s [ 11 , 12 ]. However, it is well-documented that 4CV alone is inadequate in ruling out conotruncal anomalies [ 13 15 ]. The ISUOG guideline [ 16 ] has been revised and updated to include more cardiac views that improve the efficiency of prenatal screening for CHD.…”
Section: Introductionmentioning
confidence: 99%